Computational Analysis of Adjustable Ankle Foot Orthosis for Cerebral Palsy Children - Noorul Amanina Darwin, Eka; Tardan, Giha; Halim Abdullah, Abdul (International Journal of Engineering and Technology, 2018)
Children with cerebral palsy may present several gait patterns, and the most common spastic deformity is foot equinus. One of the most effective methods of correcting foot deformity is orthotics, which involves the use of synthetic or mechanical devices worn on the feet to stabilize, heal, or prevent deformity to weak joints or bones. However, the ankle foot orthoses that is available in the market are usually fixed and not flexible. The main aim of this project was to design an adjustable ankle foot orthosis with adjustable ankle flexion and to investigate the effects of shell thickness of the foot and shank to promote optimum product. Proper engineering design process was developed in this project at several phases including the idea generation and conceptualization, evaluation of concept using Pugh Method, finite element model and analysis, and also the fabrication of the prototype using 3D printing technology. Variation of shell thickness of the foot and shank part was analyzed to predict the optimum thickness of the product. Results show that the model with .5 mm of shell thickness produces the best findings. The maximum value of von misses stress was predicted at 45.7 MPa and 4.7 MPa for the foot and shank part, respectively. Prototype model of the adjustable foot orthosis was successfully fabricated using 3D printing technology.Â Â